Use of antibiotics in poultry and poultry farmers- a cross-sectional survey in Pakistan - Um e Habiba; Amjad Khan; Elia John Mmbaga; Ivan Robert Green; Muhammad Asaduzzaman (Frontiers Media S.A., 2023)
BackgroundAntimicrobial resistance (AMR) which has been ascribed to be due to community carriage of antibiotic-resistant bacteria is highly prevalent in the WHO South-East Asia region. One of the major reasons for this is the misuse of antibiotics in animal farming practices and at the community level, which threatens both human and animal health. However, this problem of antibiotic misuse in poultry farms and in respective farmers is not well studied in countries like Pakistan.MethodsWe conducted a cross-sectional study in rural Punjab to explore the current practices of antibiotic use in poultry and poultry farmers, associated factors, their healthcare-seeking behavior and biosecurity practices.ResultsIn the context of antibiotic use for poultry, 60% comprised of Colistin sulfate and Amoxicillin trihydrate whereas Colistin is considered as the last resort antibiotic. In addition, the significant consumption of antibiotics in poultry farms (60%) and poultry farmers (50%) was without prescription by either human health physicians or veterinarians. Most of the farms (85%) had no wastewater drainage system, which resulted in the direct shedding of poultry waste and antibiotic residue into the surrounding environment. The lack of farmers' education, professional farm training and farming experience were the most significant factors associated with antibiotic use and knowledge of AMR.ConclusionOur study findings show that it is necessary for an integrated AMR policy with the inclusion of all poultry farmers to be educated, a mass awareness program to be undertaken and that strict antibiotic usage guidelines be available to them. Such initiatives are also important to ensure food safety and farm biosecurity practices.